(untitled) (Sains Humanika, 2018)
This study aims to evaluate the suitability of the Scenario Based Learning Module (SBL), which has been designed in the topic of Problem Solving Models. The study also aims to examine the advantages of SBL in universities and secondary education levels. In addition, this study was conducted to find out the barriers and constraints in the designated SBL. Lecturers from a university and a secondary school participated in this study which is conducted as an interview. The interview is aimed to gather information on the suitability and features of the module, as well as the advantages and obstacles in the SBL module. The data obtained from the interviews are qualitatively analyzed through the transcription process. The findings show that the modules are designed to be practiced at university level among students. The findings also show that the module has many advantages in terms of understanding the learning content, thinking skills and problem solving skills, social and collaborative skills and intrinsic motivation of students. Additionally, obstacles and constraints that exist in SBL are also discussed. This study benefits from the perspective of providing information on the suitability, advantages and obstacles of SBL for the Problem Solving course in Chemistry Education. In fact, university lecturers and secondary school teachers can take this study as a reference for SBL applications in teaching and learning. University students can also benefit from the SBL module designed and the results of this study.